COMPARATIVE EVALUATION OF INCIDENCE, SEVERITY, AND RELATION OF SORE THROAT AFTER ENDOTRACHEAL INTUBATION AT DIFFERENT CUFF PRESSURES - Kundra, Tanveer Singh; Berry, Deepak (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The primary objective of the study was to evaluate and compare the incidence, severity, and relation of sore throat after endotracheal intubation at different cuff pressures. The secondary objective of the present study was to evaluate whether regular monitoring of cuff pressure has any additional advantage during surgical procedures. Methods: Study design – A prospective, comparative, and randomized study. Group A – 25 female patients of age 20–35 where cuff pressure was kept at 15 cm H2O. Group B – 25 female patients of age 20–35 where cuff pressure was kept at 20 cm H2O. Group C – 25 female patients of age 20–35 where cuff pressure was kept at 25 cm H2O. Group D – 25 female patients of age 20–35 where cuff pressure was kept at 30 cm H2O. The patient was visited at 24 h, 48 h, and 72 h following extubation and enquired about the incidence of sore throat. Results: The incidence and severity of sore throat ranged from as low as 16% in group A to as high as 60% in group D at 24 h. Groups B and C showed incidences of 28% and 40%, respectively. The incidence of sore throat was found to be 12% in group A to as high as 40% in group D at 48 h postoperatively, which was further decreased to just one patient with a scratchy feeling in group A and three patients in group D at 72 h with incidence ranging from 4% to 12% only. Conclusion: As the cuff pressure goes on increasing, the incidence and severity of sore throat also increase, and cuff pressure should be monitored and regulated continuously. Moreover, the cuff pressure should not exceed 25 cm of H2O to minimize post-operative sore throat.